Guidance for Ethical Leadership in Nursing Codes of Ethics: An Integrative Review. - Schick-Makaroff, Kara; Storch, Janet L. (Nursing Leadership (1910-622X), 2019)
There has been limited attention to ethical leadership for formal nurse leaders around the world. Assuming that codes of ethics provide meaningful standards of what is expected of health professionals, what specific guidance for ethical leadership is available to formal nurse leaders in national nursing codes of ethics? We conducted an integrative review of national nursing codes of ethics for 131 member countries of the International Council of Nurses (ICN). In the ICN Code, nurse managers/ leaders are highlighted for their role in ethical practice. With the exception of the US, no other country code focuses as much attention on formal nurse leaders. While all country codes (except the United States) implicitly group nurses, practitioners and managers together, most codes do not provide meaningful guidance for formal nurse leaders. The level of ethical guidance provided to formal nurse leaders in national nursing codes of ethics is lacking. However, creating a separate code of ethics for formal nurse leaders is not the answer. Rather, including specific guidance in nursing codes of ethics not only informs nurses about what they can expect of nurse leaders but also allows formal nurse leaders to use the code with their own senior leaders, conveying what their professional body expects of them.